Detecting hazardous situations faced by presbycusic pedestrians in cities: an audio-texture approach - Faten Hussein; Raja Ghozi; Mériem Jaïdane; Jean-Pierre Péneau (Ambiances)
Within a universal context of an aging population along with an increasing consciousness regarding senior pedestrians’ safe access to the city, we examine the case of seniors affected by presbycusis, specifically their altered perceptions of the urban sonic ambiances during their daily journeys through the city. In this study, we present the urban configurations in which alarming situations were encountered by senior pedestrians suffering from presbycusis. We then construct an experimental protocol correlating collected data including audio signals, commented walks and physiological measurements of stress level generated while crossing the urban configurations previously identified. This cross-analysis process may provide urban planners with two-dimensional graphic representations intended to detect hazardous situations in order to anticipate them and minimize their effects.